Porphyrin biosynthesis in Euglena gracilis-IV. An endogenous factor controlling the enzymic synthesis of porphyrinogens and its possible role in the treatment of some porphyrias - De Geralnik, A.A.J. (1981)
1. 1. Preliminary experiments with Euglena gracilis indicated that an endogenous factor which modified enzymic synthesis of porphyrinogens from PBG, was present in Homogenates (H) and Supernatant (S) fractions. 2. 2. When H or S was stored at 4-6°C, enzymic activity underwent an apparent spontaneous activation, increasing by as much as 7.5-8 times after 14 and 22 days of aging respectively. 3. 3. Experiments were carried out to detect, isolate and identify this factor. S and H were heated and the effect of the protein free supernatants (Hø,Sø) on activity were tested. By gel filtration of H and S, a low molecular weight compound (FH, FS) was separated, and the activity of the eluated protein (PrH, PrS) was enhanced 10-12 times. 4. 4. Addition of either Hø, Sø, FH or FS to different E. gracilis preparations increased their activities, suggesting the existence of a low molecular weight, heat-stable factor which would act stimulating enzymic synthesis of porphyrinogens. However some differences in the properties of the factor present in Hø or Sø and that present in FH or FS were observed. 5. 5. Studies on the FH and FS, confirmed that the factor was heat-stable, upon storage at 4°C its activation properties were not modified; but they were destroyed by basic or acid treatment. 6. 6. The same degree of activation as that produced by FH and FS on H, S, PrH and PrS, was obtained by replacing the factor solution by 10-7M folic acid or 10-3-10-2M Gluthation (GSH); however, neither the factor nor folic acid or GSH has any effect on the pellet enzyme, either bound to the membrane or solubilized by means of a chaothropic agent. 7. 7. The potential use of this factor in the treatment of acute porphyrias was indirectly investigated, by treating acute intermittent porphyria patients in early or acute attack with folic acid; after its oral administration at a dose of 30 mg daily for not longer than 10 days, both biochemical and clinical recovery followed. 8. 8. A scheme to explain the role of this factor in acting and controlling porphobilinogenase activity in E. gracilis is proposed. © 1981.